The Book of Jeremiah: composition, reception, and interpretation - Lundbom, Jack R.; Evans, Craig A.; Anderson, Bradford A. (Supplements to Vetus Testamentum, 2018)
Intro -- Contents -- Preface -- List of Contributors -- Part 1 General Topics -- Chapter 1 The Pen of Scribes: Writing, Textuality, and the Book of Jeremiah -- Chapter 2 Jeremiah Among the Prophets -- Chapter 3 Jeremiah - "The Prophet like Moses"? -- Part 2 Issues in Interpretation -- Chapter 4 Jeremiah at Mizpah of Benjamin (Tell en-Naṣbeh): The Archaeological Setting -- Chapter 5 Messianic Expectations in the Book of Jeremiah? The Productive Memory of David -- Chapter 6 Sagacious Divine Judgment: Jeremiah's Use of Proverbs to Construct an Ethos and Ethics of Divine Epistemology -- Chapter 7 Structure in the Confessions of Jeremiah -- Chapter 8 Reconsidering the "New Covenant" in Jeremiah 31:31-34 -- Chapter 9 Yet Another New Covenant: Jeremiah's Use of Deuteronomy and שוב שבות/שבית in the Book of Consolation -- Chapter 10 The Rechabites in the Book of Jeremiah and Their Historical Roots in Israel -- Chapter 11 Language and Rhetoric in Jeremiah's Foreign Nation Oracles -- Chapter 12 What is Israel's God Up To among the Nations? Jeremiah 46, 48, and 49 -- Part 3 Textual Transmission and Reception History -- Chapter 13 The Text of Jeremiah (MT and LXX) -- Chapter 14 Texts of Jeremiah in the Qumran Library -- Chapter 15 Jeremiah in Jesus and the New Testament -- Chapter 16 Jeremiah in Targum -- Chapter 17 Jeremiah in the Peshitta -- Chapter 18 Jeremiah in the Old Testament Apocrypha and Pseudepigrapha -- Chapter 19 Jeremiah and His Book in Josephus's Writings -- Chapter 20 Jeremiah in the Latin -- Chapter 21 Medieval Christian Interpretation of the Book of Jeremiah -- Part 4 Jeremiah and Theology -- Chapter 22 Jeremiah as Mediator of the Covenant -- Chapter 23 Jeremiah's God Has a Past, a Present, and a Future -- Chapter 24 God and Place in Jeremiah -- Index of Modern Authors -- Index of Scripture and Other Ancient Writings